Pharmaceutical regulation under market integration through parallel trade - Laura Birg (Canadian Journal of Economics/Revue canadienne d'économique, 2023)
In this paper, I study the effect of parallel trade (cross-border resale of goods without the authorization of the manufacturer) on pharmaceutical regulation. Governments may restrict prices directly (price caps) or limit third-party payer reimbursement for the drug (reimbursement limits). I find that parallel trade may relax regulation in the source country of parallel imports under both instruments and intensify regulation in the destination country under a reimbursement limit. I also find that parallel trade may change regulatory preferences: under no parallel trade, both the source and destination country set price caps, and under parallel trade, the source country sets a price cap but the destination country sets a reimbursement limit, thereby enforcing a higher price cap in the South. This implies that drug prices are higher under parallel trade in both source and destination countries.
Keywords: 330